Comprehensive mapping of human body skin hydration: A pilot study. Issue 2 (10th October 2018) - Cortés, Hernán; Mendoza‐Muñoz, Néstor; Galván‐Gil, Francisco A.; Magaña, Jonathan J.; Lima, Enrique; González‐Torres, Maykel; Leyva‐Gómez, Gerardo
Abstract: Background: Previous studies analyzed a series of representative anatomical regions in the human body; however, there is a wide structural and cellular variability in the constitution of the skin. Our objective was to perform a comprehensive assessment of human skin hydration throughout the largest possible area. Materials and Methods: Hydration was registered by Corneometer ® CM825 probe in 23 anatomical regions of five healthy men. Each zone was analyzed by 2‐cm segments in the supine, prone, and lateral positions. A total of 7863 measurements were registered. Results: Differences in the degree of hydration among the prone, supine, and lateral regions were observed. The chest and back showed a pattern of increased hydration toward the neck area. Higher levels of hydration were evidenced in the proximal areas and in the regions near the elbow and knee. The regions of greater mechanical wear and with greater exposure to the sun exhibited a lower degree of hydration. Conclusion: The human skin exhibited hydration patterns influenced by anatomical function and the degree of sun exposure. Detailed information of the hydration patterns could serve as reference for the design of topical products, as an indicator of their effectiveness, and for the monitoring of skin pathologies.